Multimorbidity and acute heart failure in internal medicine. (1st April 2017) - Martínez, F; Martínez-Ibañez, L; Pichler, G; Ruiz, A; Redon, J
Abstract: Aims: To analyse the characteristics of hospitalized patients for AHF, with special attention to the clustering of morbidities. Methods and results: Clinical records of patients, admitted in Internal Medicine due to AHF, during three years, were reviewed. The characteristics of patients-episodes were registered and key indicators of performance. Multiple correspondence analysis (MCA) was used to assess the distribution of morbidities. LR models were used to study clinical variables related with death or readmission. The median age was 80y, predominantly women and with multiple morbidities. As it was expected, CVRF were the main associated comorbidities followed by respiratory diseases, CKD and chronic anaemia. In the MCA, all the CVRF clustered around the origin so they explained little of the total inertia. Male sex, young age, IHD, obesity and lung disease were more common in reduced EF whereas female, older age and thyroid disease were more common in preserved EF. The confidence ellipses for death in hospitalization or during the follow-up or for readmissions overlapped, so it was not possible to identify clusters of morbidities to predict outcomes. The main causes for AHF were infections, anaemia and RVR in AF. Nearly 16% died during the hospitalization whereas 25.6% died and 56.3% were re-hospitalized during the following year after the discharge. Previous or repeated admissions to the hospital were the best single predictors for death or readmission. Conclusions: Strategies to control infections, anaemia and AF, in the outpatient settings, might help to reduce the burden of AHF, although this remains to be proven.